Comparison of the Effects of Requirement-Based and Test-Based Formative Assessment Methods on Pre-Clinical Endodontic Competence and Performance of Dental Students: Effects of Requirement-Based and Test-Based Formative Assessment - Gohari , Atefeh; Alimadadi , Hoda; Naseri , Mandana; Barikani , Mohammadmohsen; Mehrabani, Mahgol (Journal of Dental School, 2024)
Objectives This study aimed to compare the effects of requirement-based and test-based formative assessment methods on pre-clinical endodontic competence and performance of dental students. Methods This interventional field study was conducted on dental students of Shahid Beheshti Dental School in the first and second semesters of 2021 academic year (third-year students), taking practical basic endodontics 1. After receiving theoretical instructions and practical demonstrations, the students in both groups were asked to perform root canal therapy for extracted maxillary anterior and mandibular/maxillary canine teeth as part of their requirement. Their errors were assessed and recorded by two calibrated instructors. Next, group 1 students performed root canal therapy for mandibular incisors and premolars as their requirement and returned the treated teeth on a specific date every 3 weeks. Group 2 students did not have a specific requirement and only participated in an examination which included endodontic treatment of the same group of teeth treated by group 1 students at the same designated dates. The treated teeth were assessed by instructors for errors. A final examination was held at the end of the semester for both groups. The two groups were compared by independent t-test, ANCOVA, Pearson Chi-square, and Mann-Whitney tests (alpha=0.05). Results No significant difference was found between the two groups in access cavity preparation, root canal instrumentation, or obturation (P>0.05). Conclusion Requirement-based and test-based formative assessment methods had similar effects on pre-clinical endodontic competence and performance of dental students.